Los estudios de corte filológico sobre la presencia fenicia en la Península Ibérica. La investigación española hasta mediados del s. XX - Zamora López, José Ángel (Madrider Mitteilungen, 2020)
This article outlines a history of the Spanish philological research on the Phoenician presence in the Iberian Peninsula. The paper reviews the path of these studies from its first modern efforts up to the mid-twentieth century. The 1950s heralded a change in the studies and also saw the creation of the German Archaeological Institute in Madrid. In fact, this paper comes from a talk given at a conference on the history and influence of the Instituto Arqueológico Alemán de Madrid. Its aim was to review the situation of the Spanish research on this topic when the Institute was created and to analyse the further development of the studies, with a thorough review of previous research. Here we present the analysis of the early Spanish research on the subject (noting the most important connexions between pioneer Spanish scholars and German academics).